If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 6x + 24 = 9 Reorder the terms: 24 + -3x + 6x = 9 Combine like terms: -3x + 6x = 3x 24 + 3x = 9 Solving 24 + 3x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 3x = 9 + -24 Combine like terms: 24 + -24 = 0 0 + 3x = 9 + -24 3x = 9 + -24 Combine like terms: 9 + -24 = -15 3x = -15 Divide each side by '3'. x = -5 Simplifying x = -5
| 4+x=7+2 | | .4w+60=e+53 | | r+2r+3r=4 | | 4(f-8)=-16 | | 10m-21=79 | | V+15=7 | | 6z+3z=63 | | -3x+4=3 | | 8=8z | | 2000+.56x=545+73x | | -10(s+1)=63 | | 9w+4w=76+2 | | -(c-5)=0 | | 6y-14=40 | | 121y^2-3=31 | | 7w-6w=2 | | 15(t-2)=2t | | -[8x-(16x+4)]=4+(7x+3) | | (4+3x)(x+6)= | | x^3-3x^2-5x+15= | | -6=20h | | -3(2h-3)=29-h | | 14x+18x-9+5=-8x+5-9 | | 11z=16-3(10-4z) | | 9(x+2)+2=-6(x-6)-8 | | -125=-5(7-6x) | | (4+m)(2-m+3m)= | | sqrt-45+14n=n | | -3.98=x-11.24 | | y+12=4+3y | | 3x+1x=31-9+2 | | 32m^8-24m^6+8m^4= |